2019
DOI: 10.1038/s41598-019-47253-x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Hormone receptor Met is essential for ovarian maturation in the Desert Locust, Schistocerca gregaria

Abstract: Juvenile hormones (JH) are key endocrine regulators produced by the corpora allata (CA) of insects. Together with ecdysteroids, as well as nutritional cues, JH coordinates different aspects of insect postembryonic development and reproduction. The function of the recently characterized JH receptor, Methoprene-tolerant (Met), appears to be conserved in different processes regulated by JH. However, its functional interactions with other hormonal signalling pathways seem highly dependent on the feeding habits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 93 publications
4
24
0
Order By: Relevance
“…A study by Song et al (2014) described reduced Vg gene expression in the fat body, lipid accumulation in the primary oocytes, as well as a strong inhibition of oocyte maturation upon silencing LmMet and LmKr-h1 [ 6 ]. These observations are corroborated by multiple other studies performed in numerous insect species [ 13 , 23 , 24 , 25 , 27 , 29 , 31 , 32 , 33 , 34 , 38 , 62 , 63 , 64 ]. In addition to the higher LmKr-h1 transcript levels detected in fat body of adultoid females ( Figure S5A ), lower LmE93 transcript levels were observed ( Figure S5B ), which may refer to the inhibitory effect of Kr-h1 on E93 expression [ 21 , 65 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A study by Song et al (2014) described reduced Vg gene expression in the fat body, lipid accumulation in the primary oocytes, as well as a strong inhibition of oocyte maturation upon silencing LmMet and LmKr-h1 [ 6 ]. These observations are corroborated by multiple other studies performed in numerous insect species [ 13 , 23 , 24 , 25 , 27 , 29 , 31 , 32 , 33 , 34 , 38 , 62 , 63 , 64 ]. In addition to the higher LmKr-h1 transcript levels detected in fat body of adultoid females ( Figure S5A ), lower LmE93 transcript levels were observed ( Figure S5B ), which may refer to the inhibitory effect of Kr-h1 on E93 expression [ 21 , 65 ].…”
Section: Discussionsupporting
confidence: 88%
“…A recent study in the desert locust, Schistocerca gregaria , confirmed these findings, since a knockdown of Met in female adult locusts resulted in a failure to initiate Vg expression in the fat body, as well as basal oocyte growth in the ovaries. Moreover, these ds Met -treated locusts showed delayed mating behavior and were unable to oviposit [ 38 ]. In female locusts, JH is known to stimulate Vg production by inducing Vg gene transcription in the fat body [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the JH-Met-Kr-h1 signaling pathway is involved in reproduction in L. migratoria (Song et al 2014). Other studies suggest that the JH-Met-Kr-h1 signaling pathway is conserved in insects, presumably because of its universal role in regulating female reproductive development (Marchal et al 2014, Yue et al 2018, Gijbels et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the females of several insect species, a stimulatory role of the JH signaling system on vitellogenin production by the fat body and on oocyte development in the ovary is evidenced (Badisco et al, 2013). Also in adult S. gregaria females, we recently described that the JH receptor Met is necessary for ovarian maturation, vitellogenesis and associated ecdysteroid biosynthesis, making it a crucial gene in female locust reproductive physiology (Gijbels et al, 2019). In the current study, we report on the effects of an RNAi-mediated knockdown of Scg-Met and Scg-Tai on the reproductive development of adult male desert locusts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that Scg -IRP expression is regulated during the reproductive cycle and there is evidence for a stimulatory role of Scg -IRP on vitellogenesis and ovarian development in adult female desert locusts (Badisco et al, 2011). In several other insect species, complex functional interactions have been observed between the ISP and JH signaling (Badisco et al, 2013; Gijbels et al, 2019; Roy et al, 2018; Van Wielendaele et al, 2012). In the fruit fly, D. melanogaster , the expression of the insulin receptor (IR) was detected in the CA, indicating the ability of the CA to respond to changing insulin-like peptide levels.…”
Section: Discussionmentioning
confidence: 99%